Topical osmotic therapy for a prolapsed incarcerated ostomy - José Albuquerque Landim Júnior; José Valmir Moura Júnior; Humberto Bia Lima Forte; Lara Moreira Teles de Vasconcelos; Márcia Maria de Holanda Góes Bezerra (Elsevier, 2020)
Introduction: Ostomy Prolapses are common complications in ostomized patients with some studies showing a 38% incidence in pediatric population (Husain and Cataldo, 2008; Robertson et al., 2005) [1,2]. Some prolapses remain incarcerated demanding urgent surgery. In the last decades the use of osmotic agents to reduce incarcerated prolapses had been used in adult patients, but although safe, the technique was yet still unused in pediatric patients (Theofanis et al., 2017; Mohammed et al., 2013) [3,4]. Case report: Osmotic therapy with 30 g of granulated sugar was used in a five year old patient with a 12 cm long incarcerated ostomy prolapsed ileum. After the ostomic therapy the stoma edema was significantly reduced allowing manual reduction of the incarcerated strap. Discussion: The use of sugar as an osmotic agent in this patient, has proven to be effective, since it avoided performing an emergency surgery and the use of both sedation or anesthesia.